Optimization of Hybrid Distributed Generation Systems For Rural Communities in Alaska - Willman, Lindsay; Krarti, Moncef (Distributed Generation & Alternative Energy Journal, 2013)
This article summarizes the results from a feasibility study to de- sign optimal distributed generation (DG) plants for three remote com- munities in Alaska. All three of these towns have isolated electrical grids and currently rely on diesel fuel for 100% of their electricity and heating requirements. This assessment included an analysis of each communi- ty’s electrical and thermal load, a wind and solar resource evaluation, modeling and optimization of various DG systems using HOMER soft- ware, and an economic analysis of these systems. For all three of the communities, hybrid wind-diesel systems have the potential to provide reductions in the cost of energy. However, the economic feasibility of these systems is extremely site-specific. In addition to providing possible decreases in the cost of energy, these hybrid systems can also provide significant environmental benefits, such as reductions in diesel fuel use and CO2 emissions. Future research should evaluate hybrid solar/wind generators with combined-heat-and- power (CHP) diesel engines.